Diagnostic usefulness of procalcitonin as a marker of bacteremia in patients with acute pyelonephritis. (August 2013) - Ha, Young Eun; Kang, Cheol-In; Wi, Yu Mi; Chung, Doo Ryeon; Kang, Eun-Suk; Lee, Nam Yong; Song, Jae-Hoon; Peck, Kyong Ran
Abstract Background. Acute pyelonephritis (APN) is one of the most common community-acquired infections and frequently accompanies bacteremia. The purpose of this study was to investigate the diagnostic role of procalcitonin in predicting bacteremia in patients with APN. Methods. We conducted a retrospective study of patients with APN who visited the emergency department (ED) at Samsung Medical Center, Seoul. Predictors of bacteremia were analyzed and receiver operating characteristics (ROC) curves were plotted for procalcitonin, C-reactive protein (CRP), and leukocytes. Results. During the study period, a total of 147 patients who had microbiologically proven APN and available initial procalcitonin concentrations were identified. Of these, bacteremia was present in 84 patients. Multivariate analysis showed that age, hypotension, and higher procalcitonin concentrations independently predicted the presence of bacteremia. Procalcitonin had better discriminative power than CRP, as reflected by area under the ROC curve analysis (0.746 [95% CI, 0.667–0.826] vs. 0.602 [95% CI, 0.509–0.694], p = 0.02). At a cut-off value of 1.63 μg/L, procalcitonin predicted bacteremia with a sensitivity, specificity, positive predictive value, negative predictive value and accuracy of 61.9, 81.0, 81.3, 61.4 and 70.1%, respectively. Conclusion. Procalcitonin concentration could be used as a reliable marker to predict bacteremia in patients with APN in the ED.